Conceptual Integration In The Formation Of Contemporary Spanish Slang: A CognitiveLinguistic Approach - Abdullaev Marks Kamilzhanovich (Open Academia, 2025)
This study examines the cognitive mechanisms underlying contemporary Spanish slang formation through Conceptual Integration Theory (Blending Theory). Drawing on a corpus of 350 youth slang expressions from social media, online forums, and music lyrics (2015-2024), this research analyzes the types of conceptual blends structuring Spanish slang. The investigation reveals that Spanish slang creation predominantly employs double-scope (43%) and single-scope (35%) blending networks, with metaphorical and metonymic extensions as foundational operations. The analysis demonstrates how speakers compress complex conceptual relationships through blend formation, creating emergent meanings reflecting both universal cognitive patterns and culture-specific conceptualizations. Domains examined include corporeality, technological culture, emotional states, and social relationships. This research extends Conceptual Integration Theory to an understudied domain and offers applications for lexicography, language pedagogy, and translation studies
Keywords: Conceptual integration; blending; Spanish slang; cognitive linguistics